A comparative evaluation of low cycle fatigue behavior of conventional and modified Inconel 718 - Hari Krishna E.; Prasad K.; Singh V.; Kumar V. (My University, 2025)
Structural stability of the Inconel 718 is reported to enhance at temperatures above 650°C, with increase in Al/Ti and Al + Ti/Nb atomic ratios. However, no report is available on low cycle fatigue behavior of the modified compositions of the Inconel 718. The present investigation deals with comparative study of LCF behavior of the conventional and modified 718 with Al + Ti/Nb ratios of 0.294 and 0.459 respectively at 650°C. It was observed that fatigue life of the modified alloy, in terms of Coffin-Manson relationship was higher than that of the conventional one. © 2010 TIIM, India.